Preparing for the workplace : charting a course for federal postsecondary training policy - Hansen, Janet S. (National Academy Press, 1994)
Examines the division of training responsibility between public & private sector. Emphasis on what federal government can & can not do.
Keywords: Career education -- Government policy -- United States.; Postsecondary education -- United States.; Federal aid to higher education -- United States.; Labor supply -- Effect of education on.; Préparation à une carrière -- Politique gouvernementale -- États-Unis.; Enseignement postsecondaire -- États-Unis.; Aide de l'État à l'enseignement supérieur -- États-Unis.; Marché du travail -- Effets de l'éducation sur.; EDUCATION -- Higher.; Enseignement supérieur.; Formation professionnelle.; Politique de formation.; Relation formation-emploi.; Etats-Unis d'Amérique.; Career education -- Government policy; Federal aid to higher education; Labor supply -- Effect of education on; Postsecondary education; United States; Berufsbildungspolitik; Tertiärbereich; USA